2021
DOI: 10.1111/bju.15379
|View full text |Cite
|
Sign up to set email alerts
|

A panel of systemic inflammatory response biomarkers for outcome prediction in patients treated with radical cystectomy for urothelial carcinoma

Abstract: To determine the predictive and prognostic value of a panel of systemic inflammatory response (SIR) biomarkers relative to established clinicopathological variables in order to improve patient selection and facilitate more efficient delivery of perioperative systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…(6) the design type of the study is a retrospective study and prospective study. (7) the research, which is rated as high quality by the study quality evaluation system. Also, repetitive studies, letters, case reports, reviews, studies unrelated to the subject matter, experimental results from computer models, animal experiments, and theoretical experiments, and studies that could not extract available data were excluded.…”
Section: Literature Search and Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…(6) the design type of the study is a retrospective study and prospective study. (7) the research, which is rated as high quality by the study quality evaluation system. Also, repetitive studies, letters, case reports, reviews, studies unrelated to the subject matter, experimental results from computer models, animal experiments, and theoretical experiments, and studies that could not extract available data were excluded.…”
Section: Literature Search and Eligibility Criteriamentioning
confidence: 99%
“…Any pathological type of bladder cancer has a recurrence, fatal complications, and poor prognosis after treatment. At present, a lot of studies have proved that some genes, the ratio of fibrinogen to serum albumin, the percentage of neutrophils to lymphocytes, and the modified Glasgow Prognostic Score (GPS) can be used to assess the prognosis of BC (5)(6)(7). UTUC includes ureteral cancer and renal pelvic cancer, with a low incidence, accounting for less than 10% of urothelial cancers.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Previously investigated prognostic and predictive blood-based biomarkers in patients treated with RC for UC either do not offer a clinically meaningfully discriminative ability and/or lack external validation. [8][9][10][11][12][13][14][15][16] IGF-I is produced by liver cells, 17 tumor cells, and cancerassociated macrophages. 17 The IGF-I signaling pathway, including IGF-I itself, the circulating levels of IGFBPs, and its tissue receptors (IGF-IR) have been found to promote tumor cell proliferation, metastasis, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the value of inflammatory indexes including lymphocyte-to-monocyte ratio, platelet-tolymphocyte ratio, and neutrophil-to-lymphocyte ratio were estimated in new bladder cancer cases. Moreover, studies showed that these markers were the independent predictors for OS in bladder cancer (10)(11)(12). In the Glasgow prognosis model, C-reactive protein and albumin were independent prognostic factors in tumors (13).…”
Section: Introductionmentioning
confidence: 99%